2019
DOI: 10.3390/foods8080322
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Oviductus Ranae Based on PUFAs Using HPLC Fingerprint Techniques Combined with Chemometric Methods

Abstract: Oviductus Ranae is a nutritional product for both medicine and food. Its quality is uneven due to multiple factors. An efficient method was established to evaluate the quality of Oviductus Ranae using fingerprint techniques and chemometric methods based on the analysis of polyunsaturated fatty acids (PUFAs) in petroleum ether extract by high performance liquid chromatography (HPLC). During this process, 27 batches of Oviductus Ranae were analyzed by HPLC and two types of chromatographic fingerprints were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The values of the three parameters range between 0 and 1. A reliable model could be obtained if these values are the closer to 1 [26].…”
Section: Partial Least Squares Discriminant Analysismentioning
confidence: 99%
“…The values of the three parameters range between 0 and 1. A reliable model could be obtained if these values are the closer to 1 [26].…”
Section: Partial Least Squares Discriminant Analysismentioning
confidence: 99%
“…Among them, UFAs, as important bioactive substances, have excellent biological activities in regulating immunity and preventing a series of cardiovascular and cerebrovascular diseases such as hyperlipidemia, hypertension and thrombosis [ 10 , 11 , 12 , 13 , 14 ]. The content of UFA is considered to be closely related to the quality of Oviductus Ranae [ 15 ]. However, due to the influence of breeding environment, production technology and preservation conditions [ 2 ], the content of UFA in Oviductus Ranae in different regions varies, resulting in the uneven quality of Oviductus Ranae in the market [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The content of UFA is considered to be closely related to the quality of Oviductus Ranae [ 15 ]. However, due to the influence of breeding environment, production technology and preservation conditions [ 2 ], the content of UFA in Oviductus Ranae in different regions varies, resulting in the uneven quality of Oviductus Ranae in the market [ 15 ]. Therefore, it is necessary to develop an economical and convenient method to monitor the content of UFA in Oviductus Ranae to ensure its quality.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively small amount of research on the by-products, RCO is usually treated as waste, causing serious wastage of Rana chensinensis resources. In our previous research, we found that Rana chensinensis ovum oil (RCOO) was rich in a variety of unsaturated fatty acids (UFAs), and its UFA content is several times higher than that of Oviductus Ranae [ 7 ]. Currently, UFAs are attracting much attention due to their extensive physiological activities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%